2024
DOI: 10.1002/jobm.202300585
|View full text |Cite
|
Sign up to set email alerts
|

Screening biosurfactant‐producing actinomycetes: Identification of Streptomyces sp. RP1 as a potent species for bioremediation

Adilah Ayoib,
Subash C. B. Gopinath,
Nor Syafirah Zambry
et al.

Abstract: This study aimed to isolate biosurfactant‐producing and hydrocarbon‐degrading actinomycetes from different soils using glycerol–asparagine and starch–casein media with an antifungal agent. The glycerol–asparagine agar exhibited the highest number of actinomycetes, with a white, low‐opacity medium supporting pigment production and high growth. Biosurfactant analyses, such as drop collapse, oil displacement, emulsification, tributyrin agar test, and surface tension measurement, were conducted. Out of 25 positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…These results agree with Muthukumar et al (2022), who opined that emulsification is a property of biosurfactant-producing organisms. The excellent emulsification activities exhibited by the isolated bacteria in this study is also in line with Ayoib et al (2024), who revealed that emulsification indicates the presence of biosurfactants.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These results agree with Muthukumar et al (2022), who opined that emulsification is a property of biosurfactant-producing organisms. The excellent emulsification activities exhibited by the isolated bacteria in this study is also in line with Ayoib et al (2024), who revealed that emulsification indicates the presence of biosurfactants.…”
Section: Resultssupporting
confidence: 90%
“…They are excreted by many microorganisms with emulsifying activities, and are bipolar in nature. They are composed of both hydrophilic and hydrophobic parts, which allow them to interact at the oil-water interface and optimize the microbial uptake of petroleum hydrocarbons by increasing the contact area with the contaminants (Ayoib et al, 2024). Biosurfactants have the capacity to create self-assembled molecular clusters known as micelles which houses both the hydrophilic head and the hydrophobic tail.…”
Section: Introductionmentioning
confidence: 99%